Exploring the Role of Tourism Micro Clusters in Regional Economic Development (Journal of Science-Innovative Research in Uzbekistan, 2025)
Tourism micro clusters are emerging as vital elements in regional economic development, synergizing collaboration among small-scale tourism enterprises, enhancing local identity, and optimizing resource utilization. This article examines the theoretical foundations of tourism micro clusters, their characteristics, and their impact on local economies. By analyzing case studies and conducting empirical analysis, we identify best practices and potential hurdles in the quest for sustainable tourism micro clusters. Recommendations for policymakers and industry stakeholders are provided to maximize economic and social benefits.